2015
DOI: 10.1111/nph.13432
|View full text |Cite
|
Sign up to set email alerts
|

Step‐wise and lineage‐specific diversification of plant RNA polymerase genes and origin of the largest plant‐specific subunits

Abstract: SummaryProteins often function as complexes, yet little is known about the evolution of dissimilar subunits of complexes. DNA-directed RNA polymerases (RNAPs) are multisubunit complexes, with distinct eukaryotic types for different classes of transcripts. In addition to Pol I-III, common in eukaryotes, plants have Pol IV and V for epigenetic regulation. Some RNAP subunits are specific to one type, whereas other subunits are shared by multiple types.We have conducted extensive phylogenetic and sequence analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 70 publications
14
53
0
Order By: Relevance
“…These polymerases, designated Nuclear RNA Polymerase (NRP) B, D, or E in reference to Pols II, IV, and V, respectively, are comprised of 12 core subunits and approximately half of these subunits are shared by all three polymerases [42,46] (Figure 2). Current data suggests that the unique subunits of Pol IV and Pol V arose from their Pol II counterparts via many independent duplication events, starting prior to the evolution of land plants, followed by “Escape from Adaptive Conflict” sub-functionalization [4750]. Indeed, contrary to previous reports [47,48], all land plants have specialized Pol IV and Pol V complexes [49,50] with unique catalytic cores and 7 th subunits [4850].…”
Section: Composition and Evolution Of Pol IV And Pol Vmentioning
confidence: 99%
See 1 more Smart Citation
“…These polymerases, designated Nuclear RNA Polymerase (NRP) B, D, or E in reference to Pols II, IV, and V, respectively, are comprised of 12 core subunits and approximately half of these subunits are shared by all three polymerases [42,46] (Figure 2). Current data suggests that the unique subunits of Pol IV and Pol V arose from their Pol II counterparts via many independent duplication events, starting prior to the evolution of land plants, followed by “Escape from Adaptive Conflict” sub-functionalization [4750]. Indeed, contrary to previous reports [47,48], all land plants have specialized Pol IV and Pol V complexes [49,50] with unique catalytic cores and 7 th subunits [4850].…”
Section: Composition and Evolution Of Pol IV And Pol Vmentioning
confidence: 99%
“…Current data suggests that the unique subunits of Pol IV and Pol V arose from their Pol II counterparts via many independent duplication events, starting prior to the evolution of land plants, followed by “Escape from Adaptive Conflict” sub-functionalization [4750]. Indeed, contrary to previous reports [47,48], all land plants have specialized Pol IV and Pol V complexes [49,50] with unique catalytic cores and 7 th subunits [4850]. On the other hand, additional 4 th and 5 th subunits appear to be unique to flowering [4850] and seed plants [49], respectively.…”
Section: Composition and Evolution Of Pol IV And Pol Vmentioning
confidence: 99%
“…These observations led to the suggestion that, unlike phasiRNAs and miRNAs, hc-siRNAs were not universal features found in all land plants (Dolgosheina et al, 2008). However, homologs of key genes known to be responsible for hcsiRNA biogenesis and function in angiosperms clearly exist in diverse plant lineages (Zong et al, 2009;Banks et al, 2011;Huang et al, 2015;Wang and Ma, 2015;You et al, 2017). Reverse genetic analyses of these homologs, coupled with sRNA-seq analyses of the mutants, has shown that hc-siRNAs exist in the moss P. patens (Cho et al, 2008;Coruh et al, 2015), which implies that the pathway was most likely present in the last common ancestor of all land plants.…”
Section: Conservation Evolution and Annotations Of Endogenouse Sirnasmentioning
confidence: 99%
“…Approximately half of the Pol V subunits are encoded by the same genes as Pol II subunits (Ream et al, 2013; Ream et al, 2009). Remaining subunits, including the catalytic subunits (the two largest subunits), are encoded by genes that arose through duplication and sub-functionalization of ancestral Pol II subunit genes (Huang et al, 2015; Luo and Hall, 2007; Ream et al, 2009; Tucker et al, 2010; Wang and Ma, 2015). A major distinguishing feature of Pol V is the largest subunit, NRPE1, which is characterized by a long C-terminal domain (CTD), spanning ~700 amino acids.…”
Section: Introductionmentioning
confidence: 99%